Design optimisation of a shell-and-tube heat exchanger for cold energy recovery in LNG regasification - Irfansyah, Haiqal; Sofyan, Sarwo Edhy; Razali, Razali; Tamlicha, Akram (Jurnal Polimesin, 2025)
The efficient utilisation of energy resources is a key concern in industrial operations, particularly within the liquefied natural gas (LNG) sector. During the regasification process, substantial amounts of cold energy are released as LNG transitions from its liquid to gaseous state. This cold energy, often wasted by being discharged into the environment, presents an opportunity for recovery and use in various applications such as cold storage and data centre cooling. While the utilisation of LNG cold energy has been widely explored for specific applications, including data centre cooling, electricity generation, and cryogenic systems, existing studies typically focus on individual technologies rather than a comprehensive optimisation of heat exchanger design for cold energy recovery. Therefore, there remains a significant gap in optimising heat exchanger configurations that maximise cold energy extraction while enabling broader industrial integration. This study addresses that gap by optimising the design of a shell-and-tube heat exchanger to recover cold energy from the LNG regasification process at PT Perta Arun Gas, based on an LNG flow rate of 30 million standard cubic feet per day (MMSCFD). The design optimisation was performed using Aspen Exchanger Design and Rating (Aspen EDR) software. Propane was selected as the secondary fluid for extracting cold energy from LNG due to its exceptionally low-temperature performance (freezing point: -188°C) and proven safety in food-related environments. The shell-and-tube heat exchanger design was optimised by the standards and configurations defined by the TEMA designation. The resulting optimal configuration comprises a shell-and-tube heat exchanger with a tube diameter of 13 mm, a tube length of 2,550 mm, a shell diameter of 162.74 mm, a baffle pitch of 135 mm, 16 baffles, a single tube pass, and 54 tubes. This design achieves a heat transfer rate of 478.5 kW, with an estimated cost of USD 23,895.